Constitutional Retrogression in Indonesia Under President Joko Widodo's Government: What Can the Constitutional Court Do? - Satrio, Abdurrachman (The Constitutional Court of the Republic of Indonesia, 2018)
This paper examines whether constitutional retrogression, the process through which democratically elected rulers use formal legal measures gradually to undermine democracy, has occurred in Indonesia, especially during the reign of President Joko Widodo. To this end, the paper analyzes the impact of the Widodo government's policies on three fundamental requirements of a democratic state: a democratic electoral system, rights to speech and association, and the rule of law. The paper finds that Widodo's government, in its efforts to contain the threat of Islamist populism, has indeed undermined all three of these elements to varying degrees. While Indonesia's democracy may yet be saved by the Constitutional Court, an institution that Widodo's government has until now failed to control, the Court cannot save democracy by itself. Its chances of doing so will depend on public support.